Metaheuristic Optimization in Power Engineering (2nd Edition), Volume 1 - Algorithms and Power Dispatch Using MATLAB®-Based Software - Radosavljević Jordan (Institution of Engineering and Technology (The IET), 2024)
The new edition of this book in two volumes uses a MATLAB-based software package for testing and comparing methods, and includes several new and substantially revised and updated chapters.Volume 1 covers principles and key algorithms, such as genetic and swarm algorithms, gravitational and metaheuristic algorithms, power flow and power dispatch under consideration of renewable generation.Volume 2 focuses on power distribution networks, including power flow, voltage control and regulation, optimisation of generation placement and sizing, and state estimation analysis.This reference for researchers and advanced students working on power system analysis and optimization offers an overview of metaheuristic optimization approaches to solving problems in modern power systems.